The effect of flipped classroom audiovisual content on students’ talking time and speaking skills in an adult EFL class (GIST – Education and Learning Research Journal, 2024)
This action research report explores the effect of a flipped learning strategy on adult EFL students’ speaking skills. Flipped learning, or inverted learning, reverses the traditional educational model where students learn in class and practice out of it; flipped learning promotes the students’ learning of concepts and theories out of the classroom that is later practiced and applied in class under the teacher’s guidance. The primary hypothesis was that by flipping grammar explanations, students would be more prepared and have more time to interact in English and use the structures in class. This research revealed that flipped learning helped to increase student talking time in class and accuracy in grammar use. Furthermore, it shows evidence that using flipped audiovisual materials poses advantages and challenges that can potentially boost learning inside and outside the classroom.
Keywords: Student talking time; CALL; flipped learning; class preparation; Action Research; communicative skills